IMPLIKASI EIGENDOM VERPONDING TERHADAP TIMBULNYA SENGKETA HAK ATAS TANAH DI INDONESIA - Hapsari, Devi Nuzulin; Nazidah, Febrianti Putri Ainun (Asosiasi Dosen Hukum Acara Perdata (ADHAPER), 2023)
Abstract Eigendom Verponding rights should have expired and been converted to Freehold Rights by September 1980 at the latest, based on Minister of Agrarian Affairs Regulation No. 2 of 1960 in conjunction with Minister of Agrarian Affairs Regulation No. 13 of 1961. However, many holders of western land rights did not convert their rights, resulting in the former western land rights becoming abandoned and triggering disputes. This is reflected in Cassation Decision No. 934 K/Pdt/2019, which states that the Eigendom Verponding in the name of George Henrik Muller has expired, but Review Decision No. 109 PK/Pdt/2022 granted the lawsuit and established ownership rights over the disputed object. The difference in these decisions has created legal uncertainty and undermined the sense of justice. This study uses a normative juridical method with a regulatory, conceptual, and case approach. The results show that the failure to implement the conversion resulted in the termination of the Eigendom Verponding rights, and that the inconsistency of court decisions has the potential to weaken legal certainty in the national land system. Keywords: Keywords: Conversion; Eigendom Verponding; Court Decision Abstrak Hak Eigendom Verponding seharusnya berakhir dan dikonversi menjadi Hak Milik paling lambat September 1980 berdasarkan Permen Agraria No. 2 Tahun 1960 juncto Permen Agraria No. 13 Tahun 1961. Namun, banyak pemegang hak tanah barat tidak melakukan konversi, sehingga tanah bekas hak barat menjadi terlantar dan memicu sengketa. Hal ini tercermin dalam Putusan Kasasi No. 934 K/Pdt/2019 yang menyatakan Eigendom Verponding atas nama George Henrik Muller telah berakhir, tetapi Putusan Peninjauan Kembali No. 109 PK/Pdt/2022 justru mengabulkan gugatan dan menetapkan hak kepemilikan atas objek sengketa. Perbedaan putusan tersebut menimbulkan ketidakpastian hukum dan goncangan rasa keadilan. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan peraturan perundang-undangan, konseptual, dan pendekatan kasus. Hasil penelitian menunjukkan bahwa tidak dilaksanakannya konversi mengakibatkan hapusnya hak Eigendom Verponding, serta inkonsistensi putusan pengadilan berpotensi melemahkan kepastian hukum dalam sistem pertanahan nasional. Kata Kunci: Konversi; Eigendom Verponding; Putusan Hakim